Algorithm for Background Rejection using Image Residuals - Ren, H. X.; Olivera-Nieto, L.; Mitchell, Alison; Marandon, V.; Hinton, J. A. (Proceedings of Science, 2024)
Identification of Cherenkov light generated by muons has been suggested as a promising way to dramatically improve the background rejection power of Imaging Atmospheric Cherenkov Telescopes (IACT) arrays at high energies. However, muon identification remains a challenging task, for which efficient algorithms are still being developed. We present an algorithm in which, rather than identifying Cherenkov light from muons, we simply consider the presence of Cherenkov light other than the main shower image in IACT with large mirror area. We show that in the case of the H.E.S.S. array of five telescopes this approach results in background rejection improvements at all energies above 1 TeV, while keeping high gamma-ray efficiency.
CRIS-Team Scopus Importer:2025-02-04